Changes in Cellular Behaviour during In Vitro Flowering of Petunia hybrida Vilm - Mat Taha, Rosna; Abdullah, Hasniza (Malaysian Journal of Science, 2002)
Cellular activities, including Mitotic Index (MI), chromosome counts, cell doubling time (Cdt), nuclear DNA content, mean cell and nuclear areas were examined in root meristem cells of flowering plantlets of Petunia hybrida Vilm to evaluate changes occuring during flowering phase of the plantlets in tissue culture system. The main objective was to investigate the relationship between cellular activities and in vitro flowering. Leaf explants were cultured on MS medium supplemented with 1.0 mg/l IAA with combination of 1.0 mg/l zeatin, while pedicel explants were cultured on MS medium supplemented with 1.0 mg/l kinetin for flowering to occur. We found that regeneration and in vitro flowering could only be achieved when leaf explants (from 1-month - old seedlings) and pedicels (from 1-month-old intact plants) of Petunia hybrida Vihn were used. The Mitotic Index and chromosome counts increased during flowering as compared to in viva values (determined from 5 day old seedlings after standardisation of root growth being done). The cell doubling times were shorter (P<0.05), no polyploid cells were detected and cell and nuclear sizes were bigger (P<0.05) in root meristem cells of flowering plantlets as compared to root meristem cells of 5-day-old seedlings.Cellular activities, including Mitotic Index (MI), chromosome counts, cell doubling time (Cdt), nuclear DNA content, mean cell and nuclear areas were examined in root meristem cells of flowering plantlets of Petunia hybrida Vilm to evaluate changes occuring during flowering phase of the plantlets in tissue culture system. The main objective was to investigate the relationship between cellular activities and in vitro flowering. Leaf explants were cultured on MS medium supplemented with 1.0 mg/l IAA with combination of 1.0 mg/l zeatin, while pedicel explants were cultured on MS medium supplemented with 1.0 mg/l kinetin for flowering to occur. We found that regeneration and in vitro flowering could only be achieved when leaf explants (from 1-month - old seedlings) and pedicels (from 1-month-old intact plants) of Petunia hybrida Vihn were used. The Mitotic Index and chromosome counts increased during flowering as compared to in viva values (determined from 5 day old seedlings after standardisation of root growth being done). The cell doubling times were shorter (P<0.05), no polyploid cells were detected and cell and nuclear sizes were bigger (P<0.05) in root meristem cells of flowering plantlets as compared to root meristem cells of 5-day-old seedlings.Cellular activities, including Mitotic Index (MI), chromosome counts, cell doubling time (Cdt), nuclear DNA content, mean cell and nuclear areas were examined in root meristem cells of flowering plantlets of Petunia hybrida Vilm to evaluate changes occuring during flowering phase of the plantlets in tissue culture system. The main objective was to investigate the relationship between cellular activities and in vitro flowering. Leaf explants were cultured on MS medium supplemented with 1.0 mg/l IAA with combination of 1.0 mg/l zeatin, while pedicel explants were cultured on MS medium supplemented with 1.0 mg/l kinetin for flowering to occur. We found that regeneration and in vitro flowering could only be achieved when leaf explants (from 1-month - old seedlings) and pedicels (from 1-month-old intact plants) of Petunia hybrida Vihn were used. The Mitotic Index and chromosome counts increased during flowering as compared to in viva values (determined from 5 day old seedlings after standardisation of root growth being done). The cell doubling times were shorter (P<0.05), no polyploid cells were detected and cell and nuclear sizes were bigger (P<0.05) in root meristem cells of flowering plantlets as compared to root meristem cells of 5-day-old seedlings.Cellular activities, including Mitotic Index (MI), chromosome counts, cell doubling time (Cdt), nuclear DNA content, mean cell and nuclear areas were examined in root meristem cells of flowering plantlets of Petunia hybrida Vilm to evaluate changes occuring during flowering phase of the plantlets in tissue culture system. The main objective was to investigate the relationship between cellular activities and in vitro flowering. Leaf explants were cultured on MS medium supplemented with 1.0 mg/l IAA with combination of 1.0 mg/l zeatin, while pedicel explants were cultured on MS medium supplemented with 1.0 mg/l kinetin for flowering to occur. We found that regeneration and in vitro flowering could only be achieved when leaf explants (from 1-month - old seedlings) and pedicels (from 1-month-old intact plants) of Petunia hybrida Vihn were used. The Mitotic Index and chromosome counts increased during flowering as compared to in viva values (determined from 5 day old seedlings after standardisation of root growth being done). The cell doubling times were shorter (P<0.05), no polyploid cells were detected and cell and nuclear sizes were bigger (P<0.05) in root meristem cells of flowering plantlets as compared to root meristem cells of 5-day-old seedlings.